ONLINE VISIBILITY OF PHARMACY RESEARCH IN TANZANIA: A SCIENTOMETRIC STUDY - Lwoga, Edda Tandi; Sangeda, Raphael Zozimus; Sife, Alfred Said (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This scientometric analysis was carried out to map the online visibility of pharmacy research at Muhimbili University of Health and Allied Sciences (MUHAS) from 1981 to 2016. Methods: Publish or Perish software was used to collect data for 33 scientists from the School of Pharmacy at MUHAS. We retrieved data on scholars' publications, citation counts, the number of authors per publication, average citations per paper, average citations per year, h-index, g-index, contemporary H-index (Hc index) and the HI-norm index. Results: A total of 499 publications were recorded for all scholars and the most (61; 12.2%) productive was 2013. The whole study period recorded the mean relative growth rate (RGR) and doubling time (Dt) of 1.62 and 0.46 respectively. A great majority (484; 97%) of the publications were multiple-authored with nearly one third (157; 31.5%) of these being jointly contributed by six or more authors. The maximum number of citations received in a single publication was 241. The degree of collaboration among scientists was as high as 0.97. The top ranked pharmacy researchers showed variation in various metrics. Conclusion: The study findings indicate a continuous growth of pharmacy publications at MUHAS since 1981. There is a high level of collaboration among scholars and many publications have made a great impact through citations. Â